Hubungan Ekspresi Imunohistokimia CD31 dengan Subtipe Histopatologi, Lymphovascular Invasion dan Angiogenesis pada Papillary Thyroid Carcinoma - sinambela, Roy Herbon; Delyuzar; T Kemala Intan (Majalah Patologi Indonesia, 2024)
ABSTRACT Background Thyroid carcinoma is a malignancy of the thyroid gland originating from thyroid follicular cells or parafollicles. The incidence increases slowly and is rare, occurring in approximately 1% of all-body malignancies. Papillary thyroid carcinoma ( PTC ) is influenced by radiation factors, geographic variations, age, and gender. Lymphovascular invasion (LVI) is an independent predictor of lymph node metastases. Angiogenesis is the process of forming new blood vessels and estimating angiogenesis is carried out using a microscopic approach to tumor tissue microvessel density ( MVD ) through CD31 immunohistochemistry . Increased MVD is associated with poor prognosis as an endothelial marker used in calculating MVD using CD31 . Method Cross-sectional analytic study with 32 samples diagnosed with PTC from the Anatomic Pathology Unit of H.Adam Malik General Hospital, Medan. MVD is the number of small blood vessels in terms of size and diameter ( arterioles and venules) with a round lumen stained positively with CD31 which are categorized as low (1-9 blood vessels/10 LPB), moderate (10-19 blood vessels/10 LPB) and high (>20 blood vessels/10 LPB). The relationship of CD31 immunohistochemical expression with histopathological subtypes, LVI and angiogenesis was analyzed by Eta and Somers'd tests . Results There was a significant relationship between CD31 and histopathological subtype (p=0.05 ) , lymphovascular invasion and angiogenesis with a p=0.01 ( p value<0.05 ). Conclusion MVD is significantly associated with histopathological and lymphovascular subtypes . Keywords: CD31 , PTC , LVI , MVD